AMOT130 drives BMP-SMAD signaling at the apical membrane in polarized cells - Brunner, Patrizia (Mol Biol Cell, 2020)
The large isoform of the transmembrane protein angiomotin (AMOT130) controls cell proliferation and migration of many cell types. AMOT130 associates to the actin cytoskeleton and regulates tight-junction maintenance and signaling often via endosomal uptake of polarity proteins at tight junctions. AMOT130 is highly polarized and present only at the apical side of polarized cells. Here we show that bone morphogenetic protein (BMP) growth factor signaling and AMOT function are interlinked in apical-basal polarized cells. BMP6 controls AMOT internalization and endosomal trafficking in epithelial cells. AMOT130 interacts with the BMP receptor BMPR2 and facilitates SMAD activation and target gene expression. We further demonstrate that this effect of AMOT on BMP-SMAD signaling is dependent on endocytosis and specific to the apical side of polarized epithelial and endothelial cells. Knockdown of AMOT reduces SMAD signaling only from the apical side of polarized cells, while basolateral BMP-SMAD signaling is unaffected. This allows for the first time interference with BMP signaling in a polarized manner and identifies AMOT130 as a novel BMP signaling regulator.